HUBUNGAN PENGETAHUAN IBU TENTANG PIJAT OKSITOSIN DENGAN KELANCARAN PENGELUARAN ASI PADA IBU NIFAS DI KLINIK PRATAMA ANUGERAH BINJAI TAHUN 2025 - NINGSIH SAFARI, FIFI RIA; Bestari Sinaga, eliza (Universitas Aufa Royhan, 2025)
Oxytocin massage is one solution to overcome the irregularity of breast milk production. According to WHO, countries that provide exclusive breastfeeding are only 24% and are targeted to increase to 75%. The study aims to determine the Relationship between Mother's Knowledge About Oxytocin Massage and Smooth Breast Milk Production in Postpartum Mothers at the Pratama Anugrah Binjai Clinic. The type of research is quantitative research with the design used in the study using a correlation study. The population is the total number of subjects to be studied by a researcher. The sample was 30 respondents, this study was total sampling. The stages of data analysis were carried out by univariate and bivariate analysis, using the chi square test, (P = 0.02 <0.05). The results showed that those who did oxytocin massage were around (33.3%). There was irregular breast milk production (66.7%). Regarding the implementation of Oxytocin Massage. The most dominant variable influencing is the irregularity of breast milk production, namely postpartum mothers never had a chance of 20. greater for implementation that was not carried out compared to those who had done it. It is recommended for postpartum mothers to perform oxytocin massage to facilitate smooth breast milk production.